MENGEMBANGKAN JIWA KEWIRAUSAHAAN MILENIAL DENGAN MEMANFAATKAN INTERNET DI KELURAHAN TIMBANGAN, KOTA PADANGSIDIMPUAN - Sukriah, Yani; Ritonga, Nursakinah; Harahap, Mukhlis Yakup; Linda Mora, Jessica (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Based on data released by the Indonesian Internet Service Providers Association in 2018, 64.8% of Indonesia's population is internet users. The use of the internet is dominated by millennial, namely the age group born from the 1980s to the early 2000s. The high number of internet use apparently does not contribute to millennial to be creative in entrepreneurship. The Central Statistics Agency released data in 2019 which revealed that various types of unemployment were actually dominated by millennial. Based on the existing analysis, millennial in Timbangan Village has mobile devices but they have not been used to increase income. Therefore, the implementation of this Community Partnership Program needs to be held by conducting training in developing a millennial entrepreneurial spirit by utilizing the internet in Timbangan Village. The desired achievement targets in this PKM activity are: building youth independence in Timbangan Village by encouraging their intention to become entrepreneurs and maximizing youth knowledge in utilizing the internet for entrepreneurship.